Nanoelectrical characterization of individual exosomes secreted by Aβ42-ingested cells using electrostatic force microscopy. (12th October 2020) - Choi, Yeseong; Kim, Su-Mi; Heo, Youhee; Lee, Gyudo; Kang, Ji Yoon; Yoon, Dae Sung
Abstract: Quantifying the physical properties of individual exosomes containing amyloid-β42 (Aβ42 ) is crucial for a better understanding of an underpinning mechanism of Alzheimer's disease expression which is associated with the Aβ42 transfer. Because of the lack of proper tools, however, there have been very few studies on how the amount of Aβ42 affects the physical properties of exosomes. To answer the question, we investigated the physical properties of exosomes secreted by neuroblastoma by probing individual exosomes using electrostatic force microscopy. Interestingly, we observed that when the higher concentration of Aβ42 oligomers was fed to cells, the higher surface charge of the exosomes appeared. This result indicates that the exosomes contain more Aβ42 with the increase in Aβ42 concentration in cell media, implying that they serve as transport vesicles for Aβ42 . Our approach could help to better understand how the neuronal exosomes are related to the propagation of neurodegenerative diseases and to seek how to make an early diagnosis of those diseases.